Black gold - Henry, Marguerite, 1902-1997.; Dennis, Wesley (New York : Aladin Books ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1992)
A heroic small-boned horse with a will to win is finally ridden to glory by his devoted jockey.
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; Horse racing -- Fiction